2021
DOI: 10.3389/fcvm.2021.603319
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cardiac Kinetic Energy and Its Changes During Transmural Myocardial Infarction Assessed by Multi-Dimensional Seismocardiography

Abstract: Introduction: Seismocardiography (SCG) records cardiac and blood-induced motions transmitted to the chest surface as vibratory phenomena. Evidences demonstrate that acute myocardial ischemia (AMI) profoundly affects the SCG signals. Multidimensional SCG records cardiac vibrations in linear and rotational dimensions, and scalar parameters of kinetic energy can be computed. We speculate that AMI and revascularization profoundly modify cardiac kinetic energy as recorded by SCG.Methods: Under general anesthesia, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Previous experimental studies have shown significant waveform changes during acute myocardial infarction with 3-axes linear micro-accelerometers, suggesting that this methodology might be useful in the early detection of STEMI also in the clinical setting [8,29,30]. Most recently, it was demonstrated that using multi-dimensional seismocardiography, a significant drop in cardiac kinetic energy during experimental transmural myocardial infarction reflected a decrease in left ventricular contractile function [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental studies have shown significant waveform changes during acute myocardial infarction with 3-axes linear micro-accelerometers, suggesting that this methodology might be useful in the early detection of STEMI also in the clinical setting [8,29,30]. Most recently, it was demonstrated that using multi-dimensional seismocardiography, a significant drop in cardiac kinetic energy during experimental transmural myocardial infarction reflected a decrease in left ventricular contractile function [8].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that waveforms derived from seismocardiography and gyrocardiography reproduce the main events seen in left ventricular twist and strain rates obtained from echocardiography [3,7]. Experimental evidence also suggests that abnormalities in the heart function caused by myocardial infarction could be detected using this technology [8,9]. Clinical data on these techniques is still limited, but wearable seismocardiography can help to assess the clinical status of patients with heart failure using a machine learning algorithm [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, other indexes of the heart performance, not based on the FP patterns, might be derived from the SCG signal. In literature, different alternative parameters are proposed, based on the estimation of overall signal energy (either obtained from the SCG alone or in combination with data from a gyroscope or the ballistocardiogram) ( Morra et al, 2021 ), and on the evaluation of the overall waveform characteristics through the spectral and time-frequency analysis ( Becker et al, 2014 ; Taebi and Mansy, 2017 ), dynamic-time feature matching ( Zia et al, 2020 ), hidden Markov model ( Wahlstrom et al, 2017 ), evolving fuzzy neural network ( Malcangi et al, 2020 ), and graph mining algorithms ( Inan et al, 2018 ). All these techniques extract clinical information specifically from the alterations in the waveforms caused by cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The main obstacles to SCG clinical use are the instrumentation encumbrance, the lack of standardized sensor positioning, the influence of the inter- and intrasubject variability on SCG morphology, the lack of a standardized methodology to process the collected signal, and a reliable method for features extraction, useful to identify the underlying cardiac events [ 16 , 17 ]. However, recent research studies contributed to providing a deeper insight into these issues and proving the potential clinical feasibility of SCG for an early diagnosis of abnormal cardiac functions [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Precordial Vibrations Recording Using Accelerometersmentioning
confidence: 99%